Effect of different tibia angles to loading of knee during split squat - Chang, C.-H.; Chang, C.-Y.; Lin, K.-C.; Ho, C.-S. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The aim of this study was to investigate the difference of knee joint force and moment during split squats of different front tibia angles. Twelve healthy male college students performed six repetitions of four different split squat types with a standard additional load of 25% BW added using a barbell. Using 10 camera 3D motion capture system and a force plate to collect data. The peak force and moment of knee flexion (sagittal plane) were calculated by using self-designed MATLAB programs. One-way ANOVA test was undertaken using SPSS 20.0 statistical software. The analysis results of the study indicated that all kinetic parameters of the four types split squats were achieved high significant differences (p less than .000). A better understanding of different loading in specific joints and correct exercise execution during training will help protecting practitioners from sport injury.